Manners with a library book - Tourville, Amanda Doering, 1980-; Lensch, Chris (Minneapolis, Minn. : Picture Window Books, 2009)
An introduction to etiquette and proper behavior when borrowing books from the library.
Includes bibliographical references (p. 24) and index.
Keywords: Library etiquette -- Juvenile literature; Etiquette for children and teenagers; Books -- Mutilation, defacement, etc. -- Prevention -- Juvenile literature; Library etiquette; Etiquette; Books -- Mutilation, defacement, etc. -- Prevention